Report of the Steering Group on Education, Culture and Sports for the Seventh Five Year Plan (1985-90) - Planning Commission (Planning Commission, 1984)
The number of primary schools has increased from 2.09 lakhs in 195'1 to 5.5 lakhs at present. Institutions providing middle school and Secondary education have grown many times — nearly ten times in the case of the former and more than nine times in the case of the latter. Similarly, the number of colleges has increased seven times during the period.
Planning Commission Government of India
Planning Commission Government of India